Ending child marriage : a critical appraisal of Zimbabwe’s Marriages Act 1 of 2022 [Chapter 5:15] - Ngwena, Charles (University of Pretoria, 2025)
Mini-dissertation (LLM (Sexual and Reproductive Rights in Africa))--University of Pretoria, 2024.